Association of Carla- and Poty-viruses with mosaic disease of elephant foot yam - and K.N. BHAGAWATI, Y.S. AHLAWAT, R.P. PANT* (Indian Phytopathology, 2003)
The genus Amorphophallus (family Araceae) consists of 90 species but widely cultivated species in the tropics is A. companulatus. It is cultivated throughout the Indian subcontinent for vegetable purposes. The major cultivation of A. companulatus isdone in the North-eastern and southern states. Dasheen mosaic virus (DsMV) a member of potyvirus group infecting yam has been reported from several countries'. During survey in Assam, virus disease like symptoms were observed in A. companulatus. The variety Kovur showed 80 percent incidence. The symptoms include mottling, rolling and crinkling of leaves. The leaves show cup-like structure due to inward and upward rolling of leaf margins. Brownish chlorotic spots of 0.1 to 0.2 cm in diameter appear on the leaf lamina. The diseased leaves become leathery, brittle and severely reduced. Infected plants become stunted. The size and weight of corm reduced to 70 percent.